An in vitro study on the effects of nisin on the antibacterial activities of 18 antibiotics against Enterococcus faecalis. - Zhongchun Tong; Yuejiao Zhang; Junqi Ling; Jinglei Ma; Lijia Huang; Luodan Zhang (PLoS ONE, 2014)
Enterococcus faecalis rank among the leading causes of nosocomial infections worldwide and possesses both intrinsic and acquired resistance to a variety of antibiotics. Development of new antibiotics is limited, and pathogens continually generate new antibiotic resistance. Many researchers aim to identify strategies to effectively kill this drug-resistant pathogen. Here, we evaluated the effect of the antimicrobial peptide nisin on the antibacterial activities of 18 antibiotics against E. faecalis. The MIC and MBC results showed that the antibacterial activities of 18 antibiotics against E. faecalis OG1RF, ATCC 29212, and strain E were significantly improved in the presence of 200 U/ml nisin. Statistically significant differences were observed between the results with and without 200 U/ml nisin at the same concentrations of penicillin or chloramphenicol (p<0.05). The checkerboard assay showed that the combination of nisin and penicillin or chloramphenicol had a synergetic effect against the three tested E. faecalis strains. The transmission electron microscope images showed that E. faecalis was not obviously destroyed by penicillin or chloramphenicol alone but was severely disrupted by either antibiotic in combination with nisin. Furthermore, assessing biofilms by a confocal laser scanning microscope showed that penicillin, ciprofloxacin, and chloramphenicol all showed stronger antibiofilm actions in combination with nisin than when these antibiotics were administered alone. Therefore, nisin can significantly improve the antibacterial and antibiofilm activities of many antibiotics, and certain antibiotics in combination with nisin have considerable potential for use as inhibitors of this drug-resistant pathogen.